The virtue ethics of Hume and Nietzsche - Swanton, Christine, 1947- (Malden, MA : Wiley Blackwell, 2015)
Although contemporary development of virtue ethics has focused on Aristotle, other great thinkers in ethics - notably Hume and Nietzsche - also placed virtue at the center of their ethical theorizing. Moving away from ancient moral theorists, and subjectivist interpretations of Hume's and Nietzsche's thought that have reduced their impact in normative ethics, Swanton provides a fresh perspective on the ethics of both philosophers. Discussion of the moral philosophies of Hume and Nietzsche in turn leads Swanton to seek alternative versions of virtue ethics, particularly areas that have been neglected in the mainstream Aristotelian tradition. Swanton's aim is not to argue for a virtue ethics inspired by either Nietzsche or Hume, as opposed to one inspired by Aristotle. Rather, she explores other options for virtue ethics by interpreting Hume and Nietzsche as virtue ethicists and by suggesting possibilities for virtue ethics inspired by those thinkers.--Book Jacket.
Ch. 1 Interpretation as a Map -- ch. 2 Hume and Nietzsche as Response Dependence Virtue Ethicists -- ch. 3 Can Hume Be Both a Sentimentalist and a Virtue Ethicist? -- ch. 4 Hume and the Problem of Justice as a Virtue -- ch. 5 What Kind of Virtue Ethicist Is Hume? -- ch. 6 Can Nietzsche Be Both a Virtue Ethicist and an Egoist? -- ch. 7 Can Nietzsche Be Both a Virtue Ethicist and an Existentialist? -- ch. 8 What Kind of Virtue Ethicist Is Nietzsche? -- ch. 9 Humean Virtue Ethics: Virtue Ethics of Love -- ch. 10 Nietzschean Virtue Ethics: Virtue Ethics of Becoming.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Hume, David, -- 1711-1776.; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Hume, David, -- 1711-1776.; Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Ethics; Virtue; PHILOSOPHY / Ethics & Moral Philosophy; Ethics; Virtue; Electronic books; Electronic books